Perancangan Desain Karakter untuk Buku Ilustrasi Mengenai Orang-orang Toxic - Nadya Putri Rahmadina; Diana Aqidatun Nisa; Aris Sutejo (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2023)
This journal explores toxic characters that we usually encounter in friendships. Humans are social creatures who always interact with the people around them. In social relationships, we sometimes meet individuals who often harm and disturb us emotionally, which can make our mental health bad. Therefore, there is a need for educational media that discusses toxic friendships so that young people can recognize and understand toxic characters that need to be avoided. The author discusses the process of creating character designs that center on toxic characters which will be published in an illustrated book about toxic people in the hope that the character designs can provide insight into toxic friendships and how to deal with them. The characters designed explore various toxic traits that exist in fictional characters to bring these characters to life clearly. This design not only functions as a creative medium but also offers deeper education about someone's toxic behavior.